KONTRIBUSI KEPEMIMPINAN, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Pradiva Salain; Resa Adhika (Jurnal Ilmiah Satyagraha, 2025)
This research is motivated by the importance of the involvement of human resources in a business in an effort to achieve company goals, so that the role of leadership, work discipline and high work motivation is able to improve employee performance. The aim of this research is to determine the influence of leadership, work discipline and work motivation on employee performance in retail businesses in Denpasar City.This research was conducted in a retail business with a population of 131 employees and a sample size of 99 people. Determination of the sample in this study used a saturated sampling technique. Primary data collection was carried out using a questionnaire. Hypothesis testing was carried out using multiple linear regression analysis.Based on the results of the analysis, it can be concluded that: 1) leadership has a positive and significant effect on employee performance, 2) work discipline has a positive and significant effect on employee performance, 3) work motivation has a positive and significant effect on employee performance. In improving employee performance, this retail business is expected to be able to involve employees in providing ideas and making decisions, giving strict consequences to employees who come to work not according to the set hours, namely by providing sanctions and improving the family system within the company to create good relationships between employees, for example by holding family gatherings.